Comparison Aerodynamic Performance and Power Fluctuation Between Darrieus Straight-Bladed and Gorlov Vertical Axis Wind Turbines - M. Moghimi (Journal of Applied Fluid Mechanics, 2020)
All human actions necessitate energy resources. Currently, a major part of our energy requirements is supplied by fossil fuels, which are faced with uncertainties concerning their availability in the forthcoming decades. However, the combustion of fuels results in adverse environmental aftermaths. Energy of wind falls into one of the clean and renewable energy resources. Wind power is generated using horizontal and vertical axis wind turbines (HAWTs & VAWTs). VAWTs operate appropriately under low wind velocity conditions to generate power in small scales. On the other hand, numerous VAWT designs have been presented to enhance their performance in such circumstances. This study is aimed at developing cost-effective aerodynamic calculations models for both Gorlov and Darrieus straight-bladed VAWT types. Thus, DMST (double multiple stream tube) models, which act on the basis of BEM (blade element momentum) theory, have been designed for Gorlov and Darrieus VAWTs. By comparison of the results obtained with those available in the literature, the models developed are validated. Additionally, the performance of the Darrieus-type straight-bladed VAWTs was compared to that of the Gorlov VAWTs. According to the findings, although the peak power coefficient (C_P) decreased slightly for Gorlov VAWTs in comparison with the Darrieus straight-bladed type, the Gorlov rotor showed improved performance in terms of fluctuation and effectiveness based on the torque coefficient curve of helical blades.